Pengaruh Pump and Dump, Sentimen, dan Rumor Pasar terhadap Keputusan Berinvestasi di Pasar Modal Indonesia: - Andika Ahmad Fauzi; Andri Soemitra; Rahmat Daim Harahap (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
This study was conducted to determine the effects of pump and dump, sentiment and market rumors on the decision of GIS UINSU investors to invest in the Indonesia capital market. The data collection technique used is by distributing questionnaires. The sampling technique used is Simple Random Sampling. The analytical techniques used in this research are validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing using SPSS version 25. The results of this study indicate that pump and dump and market rumors have no effect on investment decisions, while sentiment affects the decision to invest in the capital market. Then the results of the F test are obtained which show that pump and dump, sentiment, and market rumors simultaneously influence the decision of UINSU GIS investors to invest in the Indonesia capital market simultaneously. Keywords: Pump and Dump, Sentiment, Market Rumors, Investing Decision